Kaposiform hemangioendothelioma with Kasabach-Merritt phenomenon successfully treated with sirolimus: A case report and literature review on pharmacological treatment - Enrique G. Villarreal; Karen Gonzalez-Moctezuma; Diego I. Rodríguez-Mendoza; Yajaira Valentine Jiménez-Antolínez; Laura Isabel Ramos-Gómez; Sara E. Ortega Alonzo (Elsevier, 2023)
Background: Knowledge on the management of kaposiform hemanigioendothelioma (KHE) with kasabach-merritt phenomenon (KMP) rely on single case reports, case series and a few retrospective studies. Case report: A 3-month old girl was admitted for a violaceous, palpable mass in the right posterior neck. Laboratory studies showed thrombocytopenia and consumptive coagulopathy with hypofibrinogenemia and raised Dimer-D values. A diagnosis of KHE with KMP was confirmed histopathologically. Treatment regimen for KMP was commenced with oral prednisone and salicylic acid, followed by oral sirolimus at 1 mg/m2/day. It led to an involution of the vascular lesion at 12-month follow-up. Conclusion: The case contributes with another example of KHE with KMP that was effectively treated with the novel mTOR inhibitor. Prospective studies for sirolimus are urged and clinical guidelines are yet to be defined.